Galectin-3 serum profile in patients with knee osteoarthrosis: association with the disease course - Humeniuk, Oksana; Stanislavchuk, Mykola; Zaichko, Nataliia (ScienceRise: Medical Science, 2018)
Aim of the work was to study the level of galectin-3 in serum in patients with osteoarthrosis of knee joints and to evaluate its association with the course of the disease. Materials and methods. We examined 141 patients with osteoarthrosis (OA) of knee joints (76.6% of women), an average age of 58.4 ± 7.91 years, a disease duration of 10.5 ± 6.50 years, an II-III radiological stage. 33.3% of patients had a combination of OA knee and hip joints. Diagnosis of OA was established on the basis of criteria ACR 1991 and recommendations EULAR (2010). The Lequesne algo-functional index, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Knee Injury and Osteoarthritis Outcome Score (KOOS) were determined. Functional disorders were evaluated by the Health Assessment Questionnaire (HAQ). The content of galectin-3 in the blood was determined by the enzyme-linked immuno sorbent assay. Results. It has been established that in 75% of patients with OA of knee joints aberrant levels of galectin-3 in the blood are detected, including 44% of subjects with a registered high level of the index (>15.8 ng/ml). The weak associative relationships between the level of galectin-3 and the age of patients and the duration of OA were established. Among patients with aberrant levels of galectin-3, persons with severe clinical manifestations of OA appeared more often. The increase in the level of galectin-3 was associated with a significant increase in the pain syndrome and the deterioration of physical function by the indexes of Lequesne, WOMAC, KOOS, HAQ. Conclusions. In patients with OA, the increase in the production of galectin-3 is a factor in the deterioration of the clinical course of the disease, the increase in pain syndrome and functional disorders. A close associative relationship was found between the level of galectin-3 and the clinical severity indexes of OA and the weak associative relationship between the level of galectin-3 and the age and duration of the disease